Analysis of Factors Affecting Sexual Behavior in Adolescents in the Porong Health Center Work Area - Lailatul Khusnul Rizki; Rizki Amalia (Jurnal Ilmiah Kesehatan, 2019)
ABSTRACT Teenagers are part of a population that has an age range between 10-19 years. Based on the 2010 Population Census the number of adolescent groups was 43.5 million or around 18% of the total population in Indonesia (WHO, 2014). Adolescence is a period where physical and psychological growth and development are so intellectual that development is quite rapid. Having a great curiosity causes teenagers to fall into risk and may have to be associated with various physical and psychosocial health problems. Therefore, it must issue health care for adolescents who can meet the health needs of adolescents who are needed to avoid premarital sex obligations at risk for adolescents. The purpose of this study was to analyze factors that influence premarital sexual behavior in adolescents.This study is a descriptive analytic study using cross sectional. The research subjects were 100 students consisting of 50 students and 50 female students. Data collection was done directly by filling out the questionnaire and analyzed using bivariate using chi square and then refined. In the knowledge variable obtained x2 count of 38.74, attitude variable x2 counted 76.07, variables supporting media x2 count 17.29, peer role variables x2 count of 56.58, the variable has a value of p 0.000 (value p <0.05) significant for premarital sex behavior in adolescents in the Porong Health Center area. As for the variable role of parents x2 count of 0.26 with a p value of 0.614 (p value> 0.05) which means there is no relationship with premarital sex in adolescents in the work area of Porong Health Center. There is a significant positive relationship between knowledge, attitude, media discussion and peer role with premarital sex in adolescents in the Porong Health Center area. Keywords: Premarital Sexual Behavior, Adolescents